A cross sectional study of the diabetes mediated GGT to HDL ratio and cognitive function in older adults - Ye Wang; Yanping Mao; Tianmei Xu; Lujie Han; Wenxuan Zhang; Wangdi Sun; Jiaxi Xu; Enyan Yu (Scientific Reports)
Abstract The rising incidence of cognitive disorders has become a significant challenge in global public health. The ratio of Gamma-glutamyl transferase (GGT) to high-density lipoprotein (HDL), associated with insulin resistance, has an unclear relationship with cognitive function. Our cross-sectional study utilized data from the NHANES database, employing the digit symbol substitution test (DSST) to assess cognitive ability. We conducted weighted linear regression, weighted mediation analysis, dose-response relationships, and subgroup analyses to investigate the link between the GGT/HDL ratio and DSST scores, with a particular focus on the mediating role of diabetes. The study included 2750 participants. After adjusting for covariates, we found that a higher GGT/HDL ratio was significantly correlated with lower DSST scores (β = −0.06, 95% CI −0.08 to −0.04, P < 0.001, P for non-linear = 0.169), and diabetes mediated the relationship between the GGT/HDL ratio and DSST scores, accounting for 13.8% of the total effect (P = 0.034). These findings suggest that in the U.S. population aged 60 and above, an increased GGT/HDL ratio is associated with an increased risk of cognitive decline, with diabetes playing a mediating role in this association.